(untitled) (Bangladesh Veterinarian, 2010)
The growth rate, milk yield, milk composition and reproductive efficiency of Jamunapari goats were studied under semi-intensive conditions. Animals were allowed to graze for 6-7 hours and concentrate (17% CP, 11 MJ/kg DM) at 400g/head/day was offered twice daily. No body measurement was different in male and female goats. The udder was capacious but pendulous. Testis length, breadth and scrotal circumference were 17.3 ± 1.5, 11.5 ± 1.7 and 42.4 ± 2.0 cm, respectively. The mean body weight at birth and at 12 months was 1.6 and 21.4 kg, respectively. The average growth rates of male and female kids were 59.4 and 48.2g/day, respectively. The overall rate of weight gain was highest in second month and lowest in 11th month. Highest milk yield was in second month and lowest in the fifth month after kidding. Lactation length was 135.4 ± 14.9 and 143.9 ± 13.2 days for does suckling one and two kids, respectively. Milk intake to growth ratio was 15.6 ± 0.2 and 12.5 ± 0.3 for the litter size of one and two, respectively. Highest milk fat, lactose and solids not fat (SNF) were in the later stage of lactation, whereas protein and minerals were similar throughout the lactation. The average age at first oestrus, age at first pregnancy and age at first kidding were 354.8 ± 17.1, 395.4 ± 29.6 and 548.6 ± 68.1 days, respectively. The average number of services per pregnancy was 1.4. The gestation length was 152.8 ± 17.6 days. The average body weight just after kidding and placenta weight were 26.7 kg and 342.4g, respectively. The overall litter size was 1.8 and 32.9, 58.2 and 8.9% of kidding produced single, twins and triplets, respectively. Sex ratio was 53.3 male to 46.7% female. Average onset of post-partum oestrus was 51 and interval from parturition to pregnancy 69.3 days. Production of Jamunapari goats was comparable with that of the Bengal goats. (Bangl. vet. 2010. Vol. 27, No. 1, 26 – 35) DOI: 10.3329/bvet.v27i1.5912